Atrial fibrillation observed in a patient with esophageal cancer treated with fluorouracil. Issue 5 (November 2019) - Moriyama, Shohei; Yokoyama, Taku; Irie, Kei; Ito, Mamoru; Tsuchihashi, Kenji; Fukata, Mitsuhiro; Kusaba, Hitoshi; Maruyama, Toru; Akashi, Koichi
Abstract: Fluorouracil (5-FU), a commonly used anticancer agent, has potent cardiotoxicity that is mediated by vascular endothelial injury and vasospasm. Here, we report a patient demonstrating atrial fibrillation (AF), which was most likely induced by vasospasm mediated by 5-FU. A 69-year-old man presented with dysphagia and was diagnosed with advanced esophageal cancer. Frequent paroxysms of atrial fibrillation (AF) were observed during combination chemotherapy including 5-FU. AF was refractory to disopyramide, but was sensitive to antianginal agents (nicorandil and nitroglycerin transdermal patch). Coronary angiography performed within the chemotherapeutic period demonstrated moderate stenosis in the right coronary artery (RCA). Severe spasm at the proximal portion of the atrial branch in RCA was induced by provocation test using acetylcholine. Our case indicated that 5-FU predisposed vasospasm in RCA and the subsequent atrial ischemia may lead to AF. <Learning objective: Fluorouracil (5-FU), a commonly used anticancer agent, induces cardiac ischemic events and sometimes leads to the paroxysms of atrial fibrillation (AF). Coronary-dilating agents should be considered for the treatment of AF which occurs after the administration of 5-FU and is refractory to antiarrhythmic agents.>